Pharmacogenomics of NSAID-Induced Upper Gastrointestinal Toxicity - McEvoy, L.; Carr, D. F.; Pirmohamed, M. (Frontiers in Pharmacology, 2021)
Non-steroidal anti-inflammatory drugs (NSAIDs) are a group of anti-inflammatory analgesics which are widely used globally for the treatment of pain and inflammation. Chronic NSAID use is associated with potentially serious gastrointestinal (GI) adverse drug reactions (ADRs). Genetic-based risk factors have been identified, serving as predictors of adverse GI events including peptic ulcer disease (PUD) and upper gastrointestinal bleeding (UGIB). Opportunities to exploit contradictory findings and knowledge gaps, including a lack of clear clinical biomarkers, offers future potential for the identification of novel genetic and non-genetic markers of clinical relevance.